Working to Live or Living to Work? Coffee Shop Employees' Perspectives on Work-Life Balance - Vivian Osbert Lee; Vicky Sharon Lie; Erris Kusumawidjaya (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to understand the experiences of coffee shop employees in balancing work-life and personal life (Work-Life Balance / WLB) through a case study on Man of Culture. This study uses a qualitative approach through in-depth interviews with four employees. The results show that work-life balance is defined as the ability to manage time, maintain boundaries between work and personal life, and is supported by work flexibility. In addition, the fulfillment of psychological needs in Self-Determination Theory (SDT), namely autonomy, competence, and social relatedness, has been shown to play an important role in supporting the creation of this balance. These findings indicate that work-life balance is not only influenced by the aspect of working time, but also by the psychological experiences of employees in the work environment.